2006
DOI: 10.1103/physrevd.74.104007
|View full text |Cite
|
Sign up to set email alerts
|

Conserved currents in gravitational models with quasi-invariant Lagrangians: Application to teleparallel gravity

Abstract: Conservation laws in gravitational theories with diffeomorphism and local Lorentz symmetry are studied. Main attention is paid to the construction of conserved currents and charges associated with an arbitrary vector field that generates a diffeomorphism on the spacetime. We further generalize previous results for the case of gravitational models described by quasi-invariant Lagrangians, that is, Lagrangians that change by a total derivative under the action of the local Lorentz group. The general formalism is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…[25,26]. Teleparallel gravity has been readdressed by Obukhov and Pereira [27] in the geometrical framework of metric-affine theories, and further reconsidered by Obukhov and Rubilar [28,29], with the purpose of investigating the transformation (covariance) properties and conserved currents in tetrad theories of gravity. They analysed the problem of consistently defining the gravitational energy-momentum and, in particular, the problem of regularization of the expression of the gravitational energy-momentum (see also Ref.…”
Section: Review Articlementioning
confidence: 99%
“…[25,26]. Teleparallel gravity has been readdressed by Obukhov and Pereira [27] in the geometrical framework of metric-affine theories, and further reconsidered by Obukhov and Rubilar [28,29], with the purpose of investigating the transformation (covariance) properties and conserved currents in tetrad theories of gravity. They analysed the problem of consistently defining the gravitational energy-momentum and, in particular, the problem of regularization of the expression of the gravitational energy-momentum (see also Ref.…”
Section: Review Articlementioning
confidence: 99%
“…(8), (12), and (27)] from various generalizations of Killing vectors, defined as the respective solutions to Eqs. (7), (11), and the system given by Eqs. (26) and (29), which can in principle be constructed in generic spacetimes.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed investigation, which I leave for future work, will involve the further study of the systems (in particular their solutions in various spacetime geometries) described in Eqs. (7), (11) and Eqs. (26), (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharif and Nazir (2008) found that energymomentum turns out to be the same in TEGR and GR for Bell-Szekeres metric. Some people (de Andrade et al 2000;Obukhov and Pereira 2003;Obukhov et al 2006;Lucas et al 2009) proposed a new concept in this regard: "Lagrangian framework in TEGR". In this framework, Maluf et al (2002) defined gravitational energy, momentum and angular momentum using the literature (Maluf 1994).…”
mentioning
confidence: 98%